2017
DOI: 10.4067/s0034-98872017001201525
|View full text |Cite
|
Sign up to set email alerts
|

Uso de sustancias psicoactivas y calidad de vida relacionada con la salud en adolescentes escolarizados

Abstract: Background The use of psychoactive substances among adolescents is a major social and public health concern. Aim To analyze association of substance abuse and multiple drug use with health-related quality of life (HRQOL) in adolescents attending a high school in Valparaiso, Chile. Material and Methods Analytical cross-sectional study conducted in a sample of adolescents attending high school. HRQOL was assessed using KIDSCREEN-52 questionnaire and substance use was measured using the Global school-based studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
2
5
0
9
Order By: Relevance
“…Drug experimentation was associated with lower HRQoL in the present sample, as observed in adolescent samples in previous studies [ 15 , 16 ]. This relationship is not clear, and one possible explanation is that other non-observed variables predispose adolescents to health-risking behaviors (e.g., experimenting with drugs, aggressive behavior, high-risk sexual behavior) that are also associated with lower HRQoL, but some were not investigated in the present study [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Drug experimentation was associated with lower HRQoL in the present sample, as observed in adolescent samples in previous studies [ 15 , 16 ]. This relationship is not clear, and one possible explanation is that other non-observed variables predispose adolescents to health-risking behaviors (e.g., experimenting with drugs, aggressive behavior, high-risk sexual behavior) that are also associated with lower HRQoL, but some were not investigated in the present study [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, recent reviews showed that physical activity [ 6 , 10 , 11 ] and screen time [ 12 ] have been positively and negatively related to HRQoL, respectively, and sports practice has shown to be even better for some of its dimensions [ 10 ]. Furthermore, a Mediterranean diet pattern has been related to increased HRQoL scores [ 6 , 13 ], and alcohol [ 14 , 15 , 16 ], tobacco [ 17 ], and illicit drug [ 15 , 16 ] use seem to be negatively related to HRQoL. Many of the lifestyle behaviors, when adopted in an unhealthy way, have responses that may negatively impact health in ways that compromise HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al, for example, conducted a systematic review of cross-sectional and longitudinal studies on the subject and found evidence that a higher level of physical activity and less time spent in sedentary behavior are associated with higher HRQoL among the general population of children and adolescents [ 13 ]. Other studies point to the following as negative indicators of HRQoL in adolescence: lack of sleep, excessive workload, drug use [ 14 ], high levels of screen time [ 15 ], use of social networks [ 16 ], excess weight [ 17 ] and use of psychoactive substances [ 18 ]. However, in addition to habits or lifestyles, there are social and psychological factors that contribute to young people’s well-being and therefore influence their HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos trabajos locales y mundiales han abordado la problemática del consumo de drogas, realizando encuestas poblacionales en adolescentes y jóvenes escolarizados, con prevalencias variables de consumo según sustancia investigada y país de origen de la investigación. La prevalencia de (15)(16)(17) consumo en dichos estudios varía ente 3 a 6% . Estas prevalencias pertenecen a grupos poblacionales no focalizados en población vulnerable.…”
Section: Resultsunclassified